Understanding Pre-Service Math Teachers’ Use of GeoGebra: The Role of Confidence, Social Pressure, and TPACK - Rosidah; M. Miftach Fakhri; Zul Jalali Wal Ikram; Fitria Arifiyanti; Guillermo Bautista (Jurusan Teknik Informatika dan Komputer, 2025)
This study investigates the determinants of pre-service mathematics teachers’ continuous intention to use GeoGebra by integrating key constructs from educational technology acceptance and pedagogical knowledge frameworks. Employing a quantitative correlational design, data were obtained from 209 pre-service teachers through a validated questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research examined the direct effects of Self-Confidence in Mathematics (SCM), Facilitating Conditions (FC), Perceived Social Pressure (PSP), and Technological Pedagogical Content Knowledge (TPACK) on Continuous Intention to Use GeoGebra (CIUG). The results revealed that SCM, PSP, and TPACK significantly influence CIUG, whereas FC did not show a significant effect. These findings underscore the importance of psychological and pedagogical readiness over infrastructural support in predicting sustained technology use. The study contributes to the literature by providing empirical evidence on the integration of internal and external factors within a unified model and suggests that teacher education programs should focus on enhancing self-efficacy, social engagement, and TPACK to support technology integration. Future research is encouraged to explore contextual and longitudinal aspects to expand the applicability of these findings across diverse educational settings.